Association between lymphocyte-to-monocyte ratio (LMR) and the mortality of HBV-related liver cirrhosis: a retrospective cohort study. Issue 8 (21st August 2015) - Zhang, Jie; Feng, Guofang; Zhao, Ying; Zhang, Juanwen; Feng, Limin; Yang, Jing
Abstract : Objective: Infection with hepatitis B virus (HBV) remains a major cause of liver cirrhosis (LC) in China. Recent reports suggest that the lymphocyte-to-monocyte ratio (LMR) is a potential biomarker for predicting clinical outcomes. In our study, we investigated if LMR can be used as a prognostic marker of mortality in patients with HBV-related LC. Design: A retrospective cohort study. Setting: HBV-infected patients with LC and patients with chronic hepatitis B infection (CHB) from the Department of Infectious Disease were enrolled and 240 healthy individuals were recruited from the healthcare centre at the First Affiliated Hospital of Zhejiang University. Participants: 479 HBV-infected patients with LC, 134 patients with CHB and 240 healthy individuals were enrolled. Primary and secondary outcome measures: The receiver operating characteristic (ROC) curve and multivariable logistic regression analysis after adjusting for total protein, albumin, total bilirubin and the model for end-stage liver disease (MELD) score were used to evaluate the power of LMR for predicting 1 year mortality in patients with LC. Results: The LMR was statistically lower in patients with LC. The MELD score and mortality were statistically higher in patients with LC compared with the CHB and control groups. The area under the ROC curve, cut-off values, sensitivity and specificity of LMR for predicting mortality LC in the training cohort were 0.817 (95% CI 0.746 to 0.888; p<0.001), 2.10, 82.6 and 78.8%, and these data were confirmed in the validation cohort. The multivariate logistic regression analysis showed that LMR was an independent predictive factor of mortality in LC (OR 2.370, 95% CI (1.070 to 5.249); p=0.033). Conclusions: Our results strongly suggest that low LMR can be considered as an independent biomarker for predicting mortality in patients with LC.